ANALISIS PROSPEKTUS INFORMASI DAN INFLASI TERHADAP UNDERPRICING SAHAM DI BEI - Endang Sulistiawati, (2021)
In quantitative research that aims to determine whether liquidity, financial leverage, profitability, company size, underwriter reputation, auditor reputation, company age, and inflation affect the underpricing of shares in IDX. This study used simple random sampling technique and obtained a sample of 107 companies listed on the IDX for the 2017-2019 period. Hypothesis testing uses linear regression analysis with variables dummy using the Eviews 10 program and a significance level of 5%. The results of the test are (1) there is an effect of liquidity on underpricing stock (2) there is no effect of financial leverage on underpricing stock (3) there is an effect of profitability on underpricing stock (4) there is an effect of company size on underpricing stock (5) there is an effect of underwriter reputation on underpricing stock (6) there is no effect of auditor reputation on underpricing stock (7) there is an effect of company age on underpricing stock (8) there is no effect of inflation on underpricing stock.